2022
DOI: 10.3390/jof8060582
|View full text |Cite
|
Sign up to set email alerts
|

Mushrooms Do Produce Flavonoids: Metabolite Profiling and Transcriptome Analysis of Flavonoid Synthesis in the Medicinal Mushroom Sanghuangporus baumii

Abstract: Mushrooms produce a large number of medicinal bioactive metabolites with antioxidant, anticancer, antiaging, and other biological activities. However, whether they produce flavonoids and, if so, how they synthesize them remains a matter of some debate. In the present study, we combined flavonoid-targeted metabolomics and transcriptome analysis to explore the flavonoid synthesis in the medicinal mushroom Sanghuangporus baumii. The S. baumii synthesized 81 flavonoids on a chemically defined medium. The multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…HPLC/LC–MS detection and metabolite database analysis showed that flavonoids in Gbtc 2 metabolites were diverse and abundant ( Bampali et al, 2021 ). As a prerequisite for the synthesis of flavonoids, the addition of phenylalanine in the medium can promote the production of flavonoids by Gbtc 2 ( Liu et al, 2022 ; Wang S. et al, 2022 ). A total of 71 flavonoids were identified, and the properties and structures of each flavonoid had certain uniqueness.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC/LC–MS detection and metabolite database analysis showed that flavonoids in Gbtc 2 metabolites were diverse and abundant ( Bampali et al, 2021 ). As a prerequisite for the synthesis of flavonoids, the addition of phenylalanine in the medium can promote the production of flavonoids by Gbtc 2 ( Liu et al, 2022 ; Wang S. et al, 2022 ). A total of 71 flavonoids were identified, and the properties and structures of each flavonoid had certain uniqueness.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression level of PAL in OE rice was remarkably higher than that in WT rice (Figure 9), and the upregulation of PAL expression promoted the accumulation of phenolic compounds in OE rice seeds. Similarly, the overexpression of SbPAL in the medicinal mushroom Sanghuangporus baumii resulted in the increased accumulation of flavonoids (Wang et al., 2022). CHS catalyzes chalcone formation from 4‐coumaryl‐CoA and three molecules of malonyl‐CoA.…”
Section: Discussionmentioning
confidence: 99%
“…The PAL genes, c85018.graph_c0 and c84792.graph_c2, in the upstream of SA biosynthesis were upregulated in hydroponics, which was contrary to the results of SA accumulation. A possible reason is that the synthesis of SA underwent multiple catalytic steps, and the intermediate products (such as trans-cinnamic acid and shikimic acid) produced during this process were also involved in the synthesis of other secondary metabolites; thus, the expression of upstream genes did not show a direct impact on the accumulation of SA [49,50]. Another interpretation could be that the hormones' biosynthesis also depended on the post-transcriptional control of genes and the regulation of protein levels [51].…”
Section: Discussionmentioning
confidence: 99%